Gerakan Tepuk Sakinah sebagai Media Internalisasi Nilai Keluarga Islam: Analisis Normatif terhadap Resistensi Sosial Digital - M Ihsan Zaki; Nur Aini Asri Devi (Lembaga Yasin AlSys, 2026)
The Tepuk Sakinah movement introduced in the Bimbingan Perkawinan program of the Ministry of Religious Affairs of the Republic of Indonesia has sparked debate and social resistance in digital spaces because it is perceived as a simplification of Islamic family values. This study seeks to address two main questions, namely the substantive meaning of Tepuk Sakinah from the perspective of Islamic family law and the normative and social implications of its use as a medium for value internalization. The research employed a normative legal method with a conceptual approach and literature analysis, enriched by a study of digital media discourse to examine the construction of meaning and public responses to Tepuk Sakinah. The findings show that the lyrics and structure of Tepuk Sakinah represent the core values of the sakinah family, namely zawaj, mītsāqan ghalīẓan, mu‘āsyarah bil ma‘rūf, musyawarah, and tarāḍin, and are therefore normatively aligned with the principles of Islamic family law. The emerging social resistance is largely driven by fragmented symbolic interpretations and the circulation of content on social media without a comprehensive educational framework, which creates an impression of trivializing Islamic family values. This study concludes that Tepuk Sakinah has the potential to function as an effective medium for value internalization if it is positioned as a supporting learning tool rather than the primary objective, and if it is integrated with policy communication strategies that are sensitive to public perceptions. The implications suggest that the development of pedagogical innovations in keluarga sakinah guidance needs to be accompanied by more comprehensive and participatory management of public discourse in digital spaces.